Три мешка хитростей - Донцова Дарья Аркадьевна (Иронический детектив, 2001)
Экземпляры: ф.8 (20220125ԁ) / Инвентарный номер: 62571 / Цена: 20.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 67 / ББК: 84(2Рос=Рус)6